2022
DOI: 10.1038/s41598-022-23767-9
|View full text |Cite
|
Sign up to set email alerts
|

5-HT-dependent synaptic plasticity of the prefrontal cortex in postnatal development

Abstract: Important functions of the prefrontal cortex (PFC) are established during early life, when neurons exhibit enhanced synaptic plasticity and synaptogenesis. This developmental stage drives the organization of cortical connectivity, responsible for establishing behavioral patterns. Serotonin (5-HT) emerges among the most significant factors that modulate brain activity during postnatal development. In the PFC, activated 5-HT receptors modify neuronal excitability and interact with intracellular signaling involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Postnatal exposure to citalopram resulted in reduced expression of 5-HT transporter in rat cortex (Maciag et al, 2006). Since 5-HT receptors modulate glutamatergic transmission and neuronal membrane excitability (Higa et al, 2022; Zhong et al, 2008a, b), if similar effects occur in mice exposed to FLX, they might contribute to alterations in the induction of long-term synaptic plasticity observed in our experiments. In earlier studies aimed at finding facilitatory effects of 5-HT on the induction of LTD in mPFC slices, a higher concentration of 5-HT was used (40-50 μM), which markedly reduced evoked responses upon application (Higa et al, 2022; Zhong et al, 2008a, b).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Postnatal exposure to citalopram resulted in reduced expression of 5-HT transporter in rat cortex (Maciag et al, 2006). Since 5-HT receptors modulate glutamatergic transmission and neuronal membrane excitability (Higa et al, 2022; Zhong et al, 2008a, b), if similar effects occur in mice exposed to FLX, they might contribute to alterations in the induction of long-term synaptic plasticity observed in our experiments. In earlier studies aimed at finding facilitatory effects of 5-HT on the induction of LTD in mPFC slices, a higher concentration of 5-HT was used (40-50 μM), which markedly reduced evoked responses upon application (Higa et al, 2022; Zhong et al, 2008a, b).…”
Section: Discussionmentioning
confidence: 70%
“…It has been shown that FLX can transfer to the fetus through the placenta, and has also been found in breast milk (Heikkinen et al, 2003, Kim et al, 2006). During brain development 5-HT acts as a main modulator of neuronal proliferation, migration, differentiation, synaptic plasticity, and apoptotic cell death (reviewed in: Higa et al, 2022; Teissier et al, 2015; Vitalis and Parnavelas, 2003). Thus, FLX-induced increase in tissue 5- HT content may interfere with the normal development of brain circuitry (reviewed in: Adjimann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Serotonergic neurons are widely distributed in the brain with high density in the hippocampus and prefrontal cortex, areas strongly associated with cognition [ 54 , 55 , 56 ] and depression [ 57 ]. Thus, it is unsurprising that serotonin and its receptors play a significant role in learning and memory processes, as well as mood regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, serotonin receptors emerged as targets in cognitive impairment and AD ( Hung and Fu, 2017 ; Andrews et al, 2018 ; Kucwaj-Brysz et al, 2021 ; Solas et al, 2021 ; Higa et al, 2022 ). 5-HT6R and 5-HT7R are the most studied serotonin receptors in this scenario due to their brain distribution and noteworthy cognitive properties in vivo ( Kucwaj-Brysz et al, 2021 ).…”
Section: Potential Targets For Drug Designmentioning
confidence: 99%